2021
DOI: 10.1002/hrm.22092
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of diplomatic careers: The shift from traditional to contemporary careers

Abstract: Career research has focused on the changing structures of careers, mainly in the private sector. Recent literature on employment patterns in the public sector suggests that career structures are evolving, gradually moving away from their signature traditional structures to contemporary ones. However, empirical evidence of this change is scarce and inconclusive. This qualitative study examines the changes currently unfolding in the career structure of the civil service by eliciting the experiences and views of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 92 publications
(115 reference statements)
0
17
0
Order By: Relevance
“…Baruch, 2014;, research on both concepts has dramatically increased (Li et al, 2021;Wiernik and Kostal, 2019). Despite the substantial amount of research on these two orientations, common misconceptions persist (Hart and Baruch, 2022). For example, it is often assumed that those with a higher BC or PC orientation are more likely to engage in all types of physical mobility, without considering differences in transition types (e.g.…”
Section: Boundaryless and Protean Career Orientationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Baruch, 2014;, research on both concepts has dramatically increased (Li et al, 2021;Wiernik and Kostal, 2019). Despite the substantial amount of research on these two orientations, common misconceptions persist (Hart and Baruch, 2022). For example, it is often assumed that those with a higher BC or PC orientation are more likely to engage in all types of physical mobility, without considering differences in transition types (e.g.…”
Section: Boundaryless and Protean Career Orientationsmentioning
confidence: 99%
“…The field also examines career systems, where careers evolve and each context (e.g. geography and sector) forms a career landscape where careers take place, locally and globally (Baruch, 2015;Gribling and Duberley, 2021;Hart and Baruch, 2022). Even those who enact careers outside traditional organizational structures, such as contract and self-employed workers, are influenced by organizations as short-term employers, competitors or market influencers (Tempest et al, 2004).…”
mentioning
confidence: 99%
“…Future studies may offer a more comprehensive cover of motivational needs and career concepts, in line with current literature (e.g., Hart and Baruch, 2022).…”
Section: Limitations and Future Research Agendamentioning
confidence: 73%
“…For example, a recent study found that over half of surveyed professionals would rather resign than return to the office full-time [ 42 ] and there has been a great deal of news coverage suggesting that ‘forcing’ employees back to the office could result in mass resignations [ 43 , 44 ]. This is particularly important for diplomatic organisations, given that recent research suggests that the traditional career model of a diplomat (joining the organisation at a young age and spending their entire career there) is beginning to change, with younger cohorts of diplomats no longer considering diplomacy a ‘career for life’ and being much less likely than older cohorts to tolerate the negative aspects of the job and more likely to leave to start a new career if they are not happy with organisational decisions [ 45 ].…”
Section: Discussionmentioning
confidence: 99%